Characterization of Contact-Type Defects in Mortar Using a Nonlinear Ultrasonic Method - Zhichao Nie; Kui Wang; Mingjie Zhao; Xiao Sun (Advances in Materials Science and Engineering)
Second harmonic generation (SHG) is one of the common techniques in the nonlinear ultrasonic test. The contact-type defects play an important role in material damage, which are hard to be detected. The traditional nonlinear parameter β used to evaluate the micro damage in material is derived from the classical stress-strain relation, which is more suitable for the anharmonicity of crystal rather than the contact-type defects. Recently, the theoretical model based on the bilinear stiffness law was derived, and the validity and applicability need to be further studied. For this purpose, by the numerical method, the contact interface in mortar is characterized based on the damage indicator γ. The relation between the excitation voltage and γ is obtained. Moreover, the effects of the crack length and orientation on the damage indicator γ are also obtained. The experimental method is also used to characterize the contact interface in mortar. Combining with the existing work, the results obtained in this article are discussed, and further conclusions can be drawn. The conclusions in this article provide potential of quantitative detection of the contact interface and quality evaluation of bonding layers in materials.